Diagnosis and management of tendinopathies in primary care. Issue 8 (August 2020) - Fitzpatrick, Daniel
Tendinopathy describes a common overuse injury occurring in tendons around the body. Due to the high incidence and prevalence, patients with tendinopathy will often present in primary care, and it is important that GPs recognise and manage these patients appropriately.